Genetic variant of TMBIM1 is associated with the susceptibility of colorectal cancer in the Chinese population - Zhang, Jie; Fu, Yiwei; Chen, Jiebin; Li, Qianjun; Guo, Huimin; Yang, Bin (Clinics and research in hepatology and gastroenterology, 2019)
•The allele G of rs992157 was significantly associated with an increased risk of colorectal cancer.•Patients with allele G were more likely to develop lymph node metastasis and distant metastasis.•The mean expression level of TMBIM1 was significantly higher in tumor tissue than in the adjacent normal tissues.•Patients with genotype GG had remarkably higher TMBIM1 expression in the tumors than those with genotype AA.•SNP rs145204276 may increase the risk of CRC possibly via up-regulation of TMBIM1. Recent meta-analysis of genome-wide association studies (GWASs) identified a novel variant rs992157 at 2q35 that was associated with colorectal cancer (CRC) in the population of European ancestry. We aimed to replicate the association of rs992157 with CRC in the Chinese population and to further determine the real susceptible gene of CRC as indicated by this variant. 824 CRC patients and 1063 healthy controls were included. The frequency of the genotype and the allele of rs992157 were compared between the patients and the controls and between different subgroups of patients classified by status of metastasis. Expression level of TMBIM1 was compared between the tumor tissue and the adjacent normal tissues collected from 43 patients during surgery. Besides, the relationship between genotypes of rs992157 and the tissue expression of TMBIM1 was analyzed. Patients were found to have significantly higher frequency of allele G than the controls (44.2% vs. 40.0%, P = 0.009; OR = 1.18). Moreover, allele G was associated with an increased risk of lymph node metastasis (P = 0.02) and distant metastasis of CRC (P = 0.04). The mean expression level of TMBIM1 was significantly higher in tumor tissue than in the adjacent normal tissues (0.0019 ± 0.00068 vs. 0.00041 ± 0.00024, P < 0.001). In addition, patients with genotype GG were found to have remarkably higher TMBIM1 expression in the tumors than those with genotype AA (0.0024 ± 0.00052 vs. 0.0015 ± 0.00078, P = 0.005). Variant rs992157 is significantly associated with the susceptibility and progression of CRC. It can increase the risk of CRC possibly via up-regulation of TMBIM1.